Dose response in the tetrazolium test for skin carcinogenicity. - Iversen, O. H. (Nature Publishing Group, 1980)
The tetrazolium test for skin carcinogenicity was performed with different doses of (i) a strong, complete carcinogen with moderate cytotoxicity, 20-methylcholanthrene; (ii) a weak carcinogen with strong cytotoxicity, the promoter 12-O-tetradecanoylphorbol-13-acetate; (iii) a strong toxic substance with very weak carcinogenicity for the skin, cantharidin; and (iv) X-rays. The dose-response relationship was determined, and the validity of the tetrazolium test was confirmed. However, substances strongly cytotoxic must be tested in small doses to avoid necrosis. The tetrazolium test should not be used on the skin to test substances carcinogenic for organs other than skin.